2011
DOI: 10.1002/app.33575
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic degradation of poly(ethylene terephthalate) in a pyrolytic two step process to obtain benzene rich oil

Abstract: Poly(ethylene terephthalate) (PET) was degraded in a two step process to obtain a valuable oil, consisting mainly of benzene. First, PET was hydrolyzed in a steam atmosphere at 450°C, and the resulting terephthalic acid was decarboxylized in the presence of CaO. By separating the two fundamental reactions of this degradation process, the hydrolysis reaction and decarboxylation, the amount of residue was reduced, and the amount of benzene obtained increased. It was found that the best results were obtained at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The enhanced production of benzene in the presence of CaO and steam is mainly attributed to the thermal depolymerization of PET, forming terephthalic acid, and the subsequent decarboxylation reactions promoted by CaO (Scheme 1c,d). The effect of steam in the absence of CaO was studied by Grause et al 29 Hydrolysis of PET was shown to produce benzene at very low yields. The high selectivity obtained in this work was feasible due to the high-temperature steam, enhancing hydrolysis reaction intermediates, and the subsequent catalytically upgrading on the CaO catalyst, downstream from the thermal reaction zone.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The enhanced production of benzene in the presence of CaO and steam is mainly attributed to the thermal depolymerization of PET, forming terephthalic acid, and the subsequent decarboxylation reactions promoted by CaO (Scheme 1c,d). The effect of steam in the absence of CaO was studied by Grause et al 29 Hydrolysis of PET was shown to produce benzene at very low yields. The high selectivity obtained in this work was feasible due to the high-temperature steam, enhancing hydrolysis reaction intermediates, and the subsequent catalytically upgrading on the CaO catalyst, downstream from the thermal reaction zone.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…Thus, other types of catalysts, such as calcium oxide (CaO), were studied in an effort to improve the oil quality. 29,30 As shown in Scheme 1d, in pyrolysis over CaO, aromatic acids can be selectively converted to aromatic hydrocarbons. The effect of steam on the conversion and selectivity of PET via steam pyrolysis (hightemperature hydrolysis) has been studied by Yoshioka and coworkers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both DMT and DMN were analyzed by GC-MS (Agilent Technologies; GC: HP6890; column: InertCap 5 MS/Sil; MS: HP5973, program: 50 C (5 min) / 5 C min À1 / 320 C). The hydrolysis of the polyesters resulted in three mass peaks for each dimethyl dicarboxylate produced, corresponding to molecules containing two 16 O isotopes, one 16 O and one 18 O isotope, or two 18 O isotopes: m/z ¼ 194, 196, and 198 for DMT and m/z ¼ 244, 246, and 248 for DMN. For instance, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The ester bonds in polyester chains are well known to be cleaved by pyrolysis and hydrolysis. Both reactions enable the depolymerization of high-molecular-weight polyesters into monomers; thus, are commonly applied for the feedstock recycling of waste polyesters such as polyethylene terephthalate (PET), [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] polybutylene terephthalate (PBT), 8,[20][21][22] and polyethylene 2,6naphthalate (PEN). 13,14,22,23 On the other hand, pyrolysis is an attractive method because it only requires heat.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, the recycling of PET has become extremely important and attracted more and more interest . Furthermore, PET undergoes thermal, thermo‐oxidative and hydrolytic degradation during melt reprocessing, which reduces its molar mass, resulting in the reduction of its viscosity, melt strength and mechanical properties. This problem severely limits the further applications and recycling of PET.…”
Section: Introductionmentioning
confidence: 99%